Uncertainty and sensitivity analysis of the QUENCH-08 experiment using the FSTC tool. (May 2022) - Stakhanova, A.; Gabrielli, F.; Sanchez-Espinoza, V.H.; Hoefer, A.; Pauli, E.
Highlights: New tool (FSTC) for uncertainty and sensitivity (U&S) analysis developed in KIT. FSTC tool was verified against URANIE platform. Different correlations should be used for U&S analysis of severe accidents (SA). Different number of samples and re-sampling could influence on correlations values. Abstract: This paper presents results of a preliminary uncertainty and sensitivity (U&S) analysis of the QUENCH-08 experiment using the Fast Source Term Calculation (FSTC) tool, which currently is under development at KIT/INR as a part of WAME project. WAME is devoted to the development of a methodology and a tool for fast and accurate source term (ST) calculation in case of severe accident at nuclear power plant (NPP). The FSTC tool is divided into 2 parts: the U&S analysis and ST prediction (using the MOCABA approach), respectively. The description of the MOCABA approach, which is implemented in FSTC tool, will be presented – together with the results of ST evaluation – in a subsequent paper. In this paper, the FSTC tool is applied in conjunction with the Accident Source Term Evaluation Code (ASTEC) (version 2.2_b) severe accident (SA) code to the U&S analysis of the QUENCH-08 experiment to demonstrate the functionality of the tool and to check the methodology's suitability for the application to a nuclear power plant.